Cause-related marketing and start-ups: moderating role of cause involvement. Issue 1 (8th March 2019) - Aggarwal, Vivek; Singh, Vinod Kumar
Abstract : Purpose: Cause-related marketing (CrM) through social campaigns is becoming one of the main strategic marketing tools for large businesses. The purpose of this study is to find out the significance of CrM for start-ups and to evaluate the moderating role of cause involvement of consumer on the impact of CrM campaigns on purchase intention of consumers. Design/methodology/approach: Both structural equation modelling and hierarchical analysis were used to evaluate the responses of 1, 425 male and female consumers in India towards CrM campaign. Findings: The results revealed that the effect of CrM campaigns on purchase intention of consumers is significantly moderated by consumers' cause involvement. Thus, companies must extend support to causes having high consumer involvement. Research limitations/implications: Based on their findings, the authors suggest finding out the effects of CrM on the long-term sustainability of the start-ups in more detail, especially in developing countries like India. The scope of this study is one country-based; thus, research findings may not be generalised. Practical implications: Small businesses that are able to understand the needs of their own communities and recognise that through their efforts they can bring large impact on social issues and will see success through their socially responsible mindset. Society today needs businesses to support good causes. The best model of CrM, especially for start-ups, is the one in which while making a payment for a service or purchasing a product, the consumer is asked to make an additional payment for the social cause. Social implications: Society today needs businesses to support good causes. CrM campaigns provide consumers a chance to help the less fortunate and do so in regular and convenient ways. The study indicates the importance of both corporate citizenship and social responsibility among small businesses. Originality/value: While the current results show that the majority of studies were based on large business, this paper shows that the CrM can be useful for start-ups, medium and small businesses also. The suggested model can be an innovative way to implement CrM without incurring any additional cost. The conclusions confirm within a wider context the role of cause involvement as a moderator of the purchase intention and can further assist start-ups and small-scale companies in designing better targeted CrM campaigns benefiting the society at large.